Genetic Variability, Heritability, Genetic Advance, Path Coefficient Analysis, and Inter-Character Relationships in Colocynth (Citrullus colocynthis [L.] Schrad.) from Southeastern Villages of the Benin Republic - A. Seraphin Zanklan (European Scientific Journal, ESJ, 2024)
Genetic improvement of crops for important traits requires reliable estimates of genetic variability. heritability and genetic advance of intending parent materials to identify traits useful in planning an efficient breeding program through selection. Hence, the effectiveness of genetic improvement of a crop depends on the variability in the morpho-agronomic traits of individual genotypes. Understanding the variation that exists will allow the breeder to determine strategies to be adopted in his breeding program. The objectives of the present study were to estimate the magnitude of genetic variability and advance, heritability and inter-character relationships by simple correlations and path coefficient analysis in 40 local colocynth genotypes from Southeastern Benin. The experiment was carried out in a randomized complete block design with three replications in three locations for three years. 34 morpho-agronomic traits were observed in each genotype. Analysis of variance revealed that effects of genotype, genotype by year or location and genotype by year by location interactions were significant (p ≤ 0.01 or 0.05) for all the characters. Phenotypic coefficients of variation (PCV) values were relatively greater than genotypic coefficients of variation (GCV) for all traits. High magnitude of phenotypic and genotypic coefficients of variation as well as high heritability along with high genetic advance were recorded particularly for qualitative traits. All yield components, except time to emergence, time to tailspins, leaf limb width, fruit number per plant, fruit width, seed length, seed tegument percentage and stem pubescence texture, had significant and positive correlations with yield attributes represented by thousand-seed weight (TSW) and seed number per plant (SNP). Path coefficient analysis indicated that all the characters (except leaf pubescence texture, stem pubescence texture, fruit design produced by secondary skin color and male flower size) had positive direct effects on TSW and partly SNP. Results suggested that most of the 34 quantitative and qualitative traits studied could be effectively used as selection criteria in the breeding program of Citrullus colocynthis varieties with high yield.